Gerry [videorecording (Blu-Ray)] - Van Sant, Gus; Affleck, Casey, 1975-; Affleck, Casey, 1975-; Damon, Matt; Damon, Matt (Shout Factory, 2020)
Two friends who both go by the nickname ₁Gerry₂ hike on a desert trail only to find that they've gotten lost. Without water, food, or other necessary supplies, their survival skills, and friendship, are put to the test as they try to find their way to safety.